Designing of MRPABCC5 specific CRISPR/Cas9 construct and its transient analysis using AGRODATE technique in soybean leaf discs - SAHU, SMRUTIREKHA; SACHDEV, ARCHANA; JOLLY, MONICA; KRISHNAN, VEDA; MARATHE, ASHISH; JOSE, JOSHNA; PRAVEEN, SHELLY (The Indian Journal of Agricultural Sciences, 2020)
CRISPR/Cas9 has emerged as a tool of choice to precisely edit the genes pivotal for crop improvement programmes and gene function analysis. However, one of the puzzling aspects for utilization of this technique is the stability and efficiency of the construct. In the present study, we have designed the constructs dictated by certain parameters using web tools such as CRISPRscan, RNAfold webserver and OligoAnalyzer. The construct was transiently expressed in the soybean leaf discs using a vacuum based AGRODATE method (Agrobacterium mediated Transient Expression Assay) to edit the phytate transporter gene, i.e. GmABCC5. We observed an insertion of a nucleotide producing a SNP change in an analysed leaf disc sample depicting the efficacy of the construct.